Pengaruh Kadar HB terhadap Penolakan Donor Darah Metode Apheresis di UDD PMI DKI Jakarta pada Tahun 2020-2023: Penelitian - Pierlita Rini; Ratu Milandari (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Apheresis blood donation is an innovative blood transfusion service that removes certain components and returns the rest to the donor's body. However, this process is often hampered by the hemoglobin (Hb) levels of prospective donors not meeting the requirements. This study aims to analyze the effect of Hb levels on the rejection rate of apheresis blood donations at the Jakarta Red Cross (PMI) Blood Donation Unit (UDD) for the 2020–2023 period. The research method uses a quantitative approach with secondary data from donor records, analyzed through simple regression to see the relationship between Hb levels and donor rejection. Of 7,552 prospective donors, 1,940 people (25.7%) were rejected due to abnormal Hb levels. The results show a very strong and significant relationship between Hb levels and donor rejection (R² = 0.98; p = 0.0055), with a regression coefficient of 0.3667. This means that the more donors with inappropriate Hb levels, the higher the donor rejection rate. It is concluded that hemoglobin levels are a major factor in the success of apheresis donor selection. Therefore, the Jakarta PMI Blood Donor Unit needs to increase education for prospective donors about the importance of maintaining normal Hb levels to reduce rejection rates and ensure the availability of safe and high-quality blood.